Conservatism and stock crash risk: An investigation in a frontier market - Le, Thi Ngoc Phuong; Minh, Thu Vu Thi; Hoang, Ha Thi Thu; Dung, Dinh Thuy (Edelweiss Applied Science and Technology, 2025)
This study investigates the influence of accounting conservatism on stock price crash risk. Our research data is collected from 328 non-financial listed companies on the Ho Chi Minh City Stock Exchange (HOSE) in Vietnam over a 5-year period (2019 to 2023). We employ various statistical econometric models to test our research hypothesis and enhance the accuracy of regression results. Our findings reveal a negative impact of accounting conservatism on stock price crash risk. Empirical evidence shows that higher accounting conservatism lowers stock crash risk by promoting timely loss recognition and reducing earnings manipulation. Additionally, increased profitability further diminishes crash risk, and its effect is even stronger when combined with conservative accounting, thereby stabilizing outcomes and boosting investor confidence. This study provides practical insights into the advantages of applying prudence in accounting for businesses. The findings can assist listed companies in formulating effective accounting strategies to safeguard their stock value. Additionally, they offer valuable guidance for policymakers in enhancing Vietnam’s accounting regulations and financial reporting standards.